Ajuste metabólico e respostas imunes de pacus juvenis alimentados com diferentes níveis de carboidratos e submetidos a jejum prolongado - Gimbo, Rodrigo Yukihiro [UNESP] (2015)
This study is divided in three papers formatted to be submitted and publishing. In the first one, we tested carbohydrate (CHO) levels associated to fasting and refeeding as strategy to induce catabolic and anabolic pathways of different nutrients and assist in understanding of CHO intolerance in fish; in the second, we evaluated the serum ammonia as indicator of unbalanced diets utilization; and also, in a third paper, we evaluated how fasting affect the fish immunity and the metabolic strategies adopted by fish to sustain the immune response under energy deficit conditions. The results indicate pacu use efficiently high CHO levels, once values of blood glucose and liver glycogen were similar between fish fed with 25 and 45% CHO, besides this, pacu tolerates long-term fasting (30 days), without compromise the ability of weight gain response. However, 25% CHO resulted in lower mesenteric fat accumulation and higher lipolysis (more current non-esterified fatty acids) and lower levels of triglycerides and cholesterol after 30 days feeding. After 30 days fasting, fish consumed the evaluated energy reserves, but after one day re-feeding, only reserves of liver glycogen, triglycerides and cholesterol normalized, while the tissue lipid reserves were reestablished at the end of 30 days re-feeding. The hexokinase (HK), glucokinase (GK), glucose 6-phosphate dehydrogenase (G6PDH) and aspartate aminotransferase (AST) follow the metabolic variables profile, reinforcing that pacu is able to use high CHO levels and adjust their metabolism to tolerate long-term fasting. As we used two diets with different protein/energy ratio, we tested the serum ammonia determination to validate the use of this parameter as indicator of unbalanced diets utilization in pacu. The AST activity was used to prove the occurrence of protein catabolism after feeding fish during 30 days with both diets. At the end of period, we observed increasing in serum ammonia and AST ...